THE FUNCTION OF ARTICLES IN DETERMINING THE ADDRESSEE OF A LEGAL RULE IN THE SPANISH CIVIL CODE - NOWAKOWSKA-GŁUSZAK, Anna (Comparative Legilinguistics, 2013)
The aim of the article is to present how the legal categories can determine the use of natural language in the legal discourse. It is, at the same time, an example of how we can employ the tools of cultural linguistics in Legal Linguistics. The author analyzes nominal syntax structures expressing normative subject in the Spanish Civil Code and then she indicates the factors which might determine the use of the article. At the beginning she presents the traditional point of view and concludes that it is not able to explain effectively the selection of articles in the legal text, because it does not take into consideration the structure and properties of the legal norm, especially its abstract and general character. That is why she proposes to make an analysis based on the assumptions of the cultural linguistics, especially the concept of worldview, and of the grammar on semantic base, according to the proposition of J. Wilk-Racięska, which allows for the introduction of same elements of the theory of law into the philological description, and, consequently, make it more efficient.